Rod-driven parallel-continuum robot for high-speed tracking (2025)
Continuous parallel robots are controlled by the extrusion of flexible filaments and their main characteristic is their simple and lightweight system, since it has few moving parts and low volume. Among its potential applications there are robotic manipulators, platform structure control, flexible robotics, medicine, industrial manufacturing, among others. Given the low mechanical complexity and low weight of these robots, this project was designed with the objective of adding a relative control system at high speeds for tracking moving objects